Poor Compliance with Sepsis Guidelines in a Tertiary Care Children’s Hospital Emergency Room - Moresco, Benjamin Louis; Woosley, Clinton; Sauter, Morris; Bhalala, Utpal (Frontiers in Pediatrics, 2018)
Objectives: This study aimed to assess factors related to adherence to the Pediatric Advanced Life Support (PALS) guidelines for severe sepsis and septic shock (SS) in an emergency room (ER) of a tertiary care children’s hospital. Methods: This was a retrospective, observational study of children (0-18 years old) in The Children’s Hospital of San Antonio (CHofSA) ED over one year with the International Consensus Definition Codes, version-9 (ICD-9) diagnostic codes for "severe sepsis" and "septic shock." Patients in the adherent group were those who met all 3 elements of adherence: 1) rapid vascular access with at most 1 IV attempt before seeking alternate access (unless already in place), 2) fluids administered within 15 minutes from sepsis recognition and 3) antibiotic administration started within 1 hour of sepsis recognition. Comparisons between groups with and without sepsis guideline adherence were performed using student t-test (the measurements expressed as median values). The proportions were compared using chi-square test. P value ≤ 0.05 was considered significant. Results: A total of 43 patients who visited the ED from July 2014 to July 2015 had clinically proven severe sepsis or septic shock ICD-9 codes. The median age was 5 years. The median triage time, times from triage to vascular access, fluid administration and antibiotic administration were 26, 48.5, 76 and 135 minutes respectively. Adherence to vascular access, fluid and antibiotic administration guidelines was 21%, 26% and, 34% respectively. Appropriate fluid bolus (20mls/kg over 15-20mins) was only seen in 6% of patients in the non-adherent group versus 38% in the adherent group (p=0.01). All of the patients in the non-adherent group used an infusion pump for fluid resuscitation. Hypotension and ≥ 3 organ dysfunction were more commonly observed in patients in adherent group as compared to patients in non-adherent group (38% vs. 14% p=0.24; 63% vs. 23% p=0.03). Conclusions: Overall adherence to sepsis guidelines was low. The factors associated with non-adherence to sepsis guidelines were >1 attempt at vascular access, delay in antibiotic ordering, fluid administration using infusion pump, absence of hypotension, and absence of three or more organs in dysfunction at ER presentation.